1948
DOI: 10.1029/te053i001p00027
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric electricity during disturbed weather

Abstract: From October, 1942, to May, 1946, a special investigation of, atmospheric electricity during disturbed weather was undertaken at Kew Observatory, England, with special reference to the electricity carried on rain and snow. The results obtained have been discussed in detail in a paper which is to be published as Geophysical Memoir No. 84 by the London Meteorological Office. Owing to shortage of paper and other difficulties resulting from the war it may be some considerable time before the Memoir is printed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

1951
1951
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…For each case of polarity they indicated that the charges carried by the precipitation at the Earth surthce have the same sign as that of the space charge in the subcloud layer through which the raindrops have fallen. As given by Simpson [1949], they observed the nfirror image relation between the electric field and the rain current density', that is, the field is upward when the precipitation current carries dox•n positive charges. R,st and Moore [1974] and at the ground.…”
Section: Introductionmentioning
confidence: 99%
“…For each case of polarity they indicated that the charges carried by the precipitation at the Earth surthce have the same sign as that of the space charge in the subcloud layer through which the raindrops have fallen. As given by Simpson [1949], they observed the nfirror image relation between the electric field and the rain current density', that is, the field is upward when the precipitation current carries dox•n positive charges. R,st and Moore [1974] and at the ground.…”
Section: Introductionmentioning
confidence: 99%
“…According to this mechanism, the electrification of precipitation particles is a result of the electric field. However it is seen in a figure presented by Simpson (1949) that the change in the sign of precipitation current occurred earlier than that of electric field. Namely, the result seems to have preceded the cause.…”
Section: Introductionmentioning
confidence: 99%
“…About fourty years ago, Noto (1939) found that the sign of charge on raindrops and snowflakes was opposite to that of electric field at the ground, and Simpson (1949) reported that the sign of precipitation current changed inversely against that of the electric field. The sign of electric field is defined to be positive when a positive charge exists above the ground, and that of precipitation current is defined as positive when positively charged raindrops fall.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have reported various patterns of changes in the surface electric field during rainfall (for example, Simpson, 1949;Sivaramakrishnan, 1953;Whitlock and Chalmers , 1956;Magono and Orikasa, 1960;Huzita and Ogawa, 1976). These patterns can be roughly classified into two types.…”
Section: Introductionmentioning
confidence: 99%